Development of A Knowledge-Sharing-Oriented Online Learning Model to Enhance Student Learning Outcomes - Asmara, Jimi; ., Rusijono; Kristanto, Andi; Rahayu, Imma; ., Herlina; Suseno, Jarot; Muafa, Ahsan; Iswanto, Sufandi; Kurniawan, Dydik; Kuncoro, Akhmad (Journal of Posthumanism, 2025)
This study investigates the creation of a Online learning model grounded in Knowledge Sharing to improve student learning results. The study utilizes the Lee & Owens (2004) paradigm as a framework for creating an interactive e-learning system that incorporates social media, specifically Instagram, to enhance knowledge sharing. The research employed a quasi-experimental design featuring pretest and posttest assessments involving 30 university students. Results demonstrate a notable enhancement in students’ academic performance, with a pretest mean of 66.13 and a posttest mean of 79.60, resulting in a gain score of 0.56. The model received validation from subject matter experts, attaining strong validity ratings (97.33% for content validity and 91.76% for design validity). The findings indicate that a Online learning model that integrates Knowledge Sharing helps enhance academic engagement and increasing learning outcomes.